Exploring students’ experience of ChatGPT in STEM education - Federico Valeri; Pernilla Nilsson; Anne-Marie Cederqvist (Computers and Education: Artificial Intelligence)
The rapid advances in AI technologies showed a disruptive potential in educational practices, presenting new challenges and generating new opportunities. This phenomenon has been exacerbated since the release of ChatGPT in 2022, which has permanently transformed various educational activities and sparked widespread scientific interest. Research suggests that ChatGPT can help students navigate the complexities of STEM subjects. However, only a few studies have directed attention to the use of ChatGPT in STEM subjects in upper secondary education. With the purpose of addressing this gap, the aim of this study is to explore how students experience ChatGPT for their STEM studies, encompassing their usage, perceptions, and general knowledge about this technology. Using a mixed methods approach, the data collected included a survey and semi-structured interviews involving upper secondary students. The results show widespread adoption of ChatGPT across STEM subjects among participants, particularly in biology and especially as a tool to support the understanding of concepts. Although students exhibited limited knowledge of AI, they demonstrated some effective prompting strategies to generate relevant content and tackle potential inaccuracies and hallucinations. The findings in this paper provide insights to support the exploration of students’ experiences of ChatGPT, presenting relevant topics to further research the applications of these AI technologies within STEM subjects, given their importance for future societal development.